Preoperational chronic pain impairs the attention ability before surgery and recovery of attention and memory abilities after surgery in non-elderly patients - Gu H; Deng X; Lv Y; Chen Q; Yu W (Journal of Pain Research, 2018)
Huahua Gu,1,* Xianyu Deng,2,* Yizheng Lv,1 Qian Chen,1 Weifeng Yu3 1Department of Anesthesiology, Huashan Hospital, Fudan University, Shanghai, China; 2Department of Neurosurgery, Tenth People’s Hospital of Tongji University, Shanghai, China; 3Department of Anesthesiology, Renji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, China *These authors contributed equally to this work Purpose: This study aimed to investigate the relationship of preoperative chronic pain and postoperative cognitive dysfunction (POCD) in non-elderly patients who underwent arthroscopic surgery.Materials and methods: The pain intensity was estimated using visual analog scale, and the cognitive function was assessed by Syndrom Kurz Test. The effects of preoperative chronic pain on the cognitive scales were comparatively studied between the patients of observational group (OG, with chronic pain) and control group (CG, without chronic pain) pre- and postoperatively, and followed up for 3 months.Results: A total of 57 non-elderly patients completed the study. Twenty-five patients (44%) with preoperative chronic pain were assigned to OG and 32 patients (56%) without chronic pain were assigned to CG. Preoperation chronic pain impaired the attention ability before surgery and caused less recovery of attention and memory abilities from 24 hours to 3 months after the surgery. Surgery procedures improved the attention and memory abilities and impaired the ability of numerical ability in CG patients. A postoperative pain relief in OG patients caused more recovery of cognition in addition to surgery procedure-mediated cognitive recovery. The incidence of POCD was ~3.5% and temporary at 24 hours after surgery, and disappeared at 2 weeks, 6 weeks and 3 months after the surgery.Conclusion: The incidence of POCD in non-elderly population who underwent arthroscopic surgery was low. Surgery improved the abilities of attention and memory, and impaired the ability of counting. The preoperative chronic pain distracted the attention before surgery, and reduced the recovery of attention and memory abilities during the follow-up period after the surgery in non-elderly patients. Keywords: cognition dysfunction, chronic pain, non-elderly population